Human resource management. An example in public sector/ Farah Adilla Ab Rahman - Rahman, Farah Adilla (2010)
Human resource management is defined as the policies and practices one needs to carry out the people or human resource aspects of a management position, including recruiting, screening, training, rewarding and appraising. The research discusses the practice of human resource management in the Department of Works Malaysia in managing its civil servants for the year 2009. The researcher had used primary and secondary data for example, interviews, reports and books.